Associations of sperm DNA fragmentation with lifestyle factors and semen parameters of Saudi men and its impact on ICSI outcome - Basmah Al Omrani; Nadia Al Eisa; Murid Javed; Maher Al Ghedan; Hamoud Al Matrafi; Hamad Al Sufyan (BMC, 2018)
Abstract Background Male factor infertility is quite common as 30-50% of infertility cases are due to sperm defects. The high sperm DNA fragmentation is one of the causes of male factor infertility. Many factors cause sperm DNA fragmentation and could be testicular or post-testicular. The purpose of this study was to assess relationships among sperm DNA fragmentation, lifestyle factors and semen values of Saudi men and to determine impact of sperm DNA fragmentation on ICSI cycle outcome. Methods The duration of this study was from January 2015 to June 2016. The cases with female factor infertility were excluded. In total 94 couples were selected for investigation. The study parameters were male age, body mass index, smoking, semen values, % sperm DNA fragmentation, fertilization rate and pregnancy outcome. The ICSI procedure was performed in all patients per standard protocol. The semen samples were grouped based on % sperm DNA fragmentation into < 15%, 15-30 and > 30% which corresponded to low, moderate and high sperm DNA fragmentation, respectively. Results There was no difference in ICSI outcome in low and moderate sperm DNA fragmentation, however, in high sperm DNA fragmentation no patient achieved pregnancy. In this study, 53.19% Saudi men had low, 32.98% moderate and 13.83% high DFI. Semen volume, sperm morphology and fertilization rate did not show any correlation trend with DNA fragmentation, however, sperm concentration and motility were negatively correlated in all DFI categories. The BMI was positively correlated in moderate DFI category and smoking was positively correlated with low DFI category. The age was positively correlated in moderate and high DFI categories. Conclusions The results of this study indicated that 14% Saudi men had high DNA fragmentation. The BMI was positively correlated in moderate DFI category and smoking was positively correlated with low DFI category. The age was positively correlated in moderate and high DFI categories.